2018
DOI: 10.1111/ced.13397
|View full text |Cite
|
Sign up to set email alerts
|

The Vitamin D3 analogue calcipotriol suppresses CpG-activated TLR9-MyD88 signalling in murine plasmacytoid dendritic cells

Abstract: CAL may downregulate pDCs by inhibiting TLR9-MyD88 signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Intriguingly, this expression was found decreased in D 3 -MDMs. This data is in line with other studies in which VitD3 was shown to decrease TLR9 expression in HeLa cells infected with Herpes simplex virus-1 [47], in monocytes [48], in murine plasmacytoid DCs [49], and in DENV-2 infected Mo-DCs [50]. We also found that VitD3 reduced the production of ROS at 2 hpi in D 3 -MDMs after infection with DENV-2.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 93%
“…Intriguingly, this expression was found decreased in D 3 -MDMs. This data is in line with other studies in which VitD3 was shown to decrease TLR9 expression in HeLa cells infected with Herpes simplex virus-1 [47], in monocytes [48], in murine plasmacytoid DCs [49], and in DENV-2 infected Mo-DCs [50]. We also found that VitD3 reduced the production of ROS at 2 hpi in D 3 -MDMs after infection with DENV-2.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 93%
“…Conventional psoriasis therapies, including topical applications of vitamin D analogs or vitamin A analogs, have also been shown to exert their anti-inflammatory effects by modulating TLR function. Vitamin D3 downregulates the expression of TLR2, TLR4, and TLR9 and suppresses TLR9-mediated cytokine production in human monocytes [115], and the vitamin D analog calcipotriol attenuates CpG-mediated elevation of TLR9 and MyD88 expression in pDCs [116]. Retinoids, namely, vitamin A and its metabolites, have been used to treat psoriasis since the 1980s.…”
Section: Tlr-targeted Therapiesmentioning
confidence: 99%
“…TLR1, TLR2, TLR4, TLR5, and TLR6 are located on the cell surface but TLR3, TLR7, TLR8, and TLR9 are within endosomes [ 40 ]. Furthermore, TLR2 recognizes bacterial lipoproteins, TLR4 recognizes lipopolysaccharides (LPS), and TLR9 recognizes CpG-containing DNA (CpG-ODN) [ 41 , 42 ].…”
Section: Toll-like Receptormentioning
confidence: 99%